Machine and sovereignty : for a planetary thinking - Hui, Yuk, 1985- (Minneapolis, MN : University of Minnesota Press, 2024)
"Machine and Sovereignty offers a future-oriented mode of political thought that encompasses the unprecedented global challenges we are confronting: the rise of artificial intelligence, the ecological crisis, and intensifying geopolitical conflicts. Arguing that a new approach to planetary thinking is urgently needed, Yuk Hui presents new epistemological and technological frameworks for understanding and rising to the crises of our present and our future"--
Planetary thinking: 1- thinking beyond the configuration of modern nation-states; 2- formulating a language of coexistence on the same planet; 3- developing a new framework that will enable us to go beyond the question of territory, respond to the current ecological crisis, and reverse the accelerated entropic process of the Anthropocene
Recursivity and Contingency (2019) is first, followed by Art and Cosmotechnics (2021), and ending with Machine and Sovereignty, the third and final volume of this 3-volume series.
Keywords: Political science -- Philosophy; Technology -- Philosophy; Artificial intelligence -- Philosophy; Ecology -- Philosophy; Geopolitics -- Philosophy; Sovereignty